"Beautiful" and "sublime" by І. Kant within everyday experience of the city - Butsykina, Yevheniia (Ukrainian Cultural Studies, 2024)
Background. This paper explores the relevance of Kantian aesthetics, specifically his concept of the sublime, in the context of contemporary urban experience in Ukraine, particularly amidst the ongoing war. It examines how modern aesthetics engage with Kant’s ideas, with some rejecting the applicability of his notions on beauty, the sublime, and aesthetic judgment, while others affirm their importance for understanding contemporary urban experiences. Methods. The study employs a comparative and analytical methodology, examining Kantian aesthetics in relation to contemporary aesthetic theories, particularly in everyday and urban contexts. It integrates philosophical analysis, historical contextualization, and theoretical classification, engaging with key thinkers such as Kant, Hegel, Dewey, Berleant, Saito, Leddy, and Kvokačka to explore shifts in aesthetic discourse and the relevance of Kantian categories in modern aesthetic experiences. Results. The discussion highlights the contradiction inherent in the experience of the modern city, where the Kantian sublime–a concept traditionally associated with reflection and disinterested pleasure–can still be relevant, but often in a transformed or "negative" form. This is especially notable in the context of urban environments that are undergoing rapid changes due to technological advancements and social upheaval. The emergence of the "negative sublime" concept is explored as a way to describe the urban experience of modern city dwellers who, due to the chaos and overwhelming nature of their environment, may be unable to feel the traditional sense of the sublime. The author situates this discussion within the specific context of contemporary Ukrainian cities, where the ongoing war and the imposition of martial law dramatically shape daily life. The concept of the sublime is argued to be especially relevant in the analysis of grassroots commemorative practices, such as spontaneous memorials that emerge in response to war. These memorials, while ephemeral and often improvised, offer a form of aesthetic experience that resonates with Kant’s notion of the sublime–emphasizing reflective judgment and negative pleasure as people engage with public spaces marked by loss and trauma. Conclusions. Ultimately, the paper advocates for the continued use of the Kantian sublime in understanding the emotional and aesthetic impacts of the modern urban environment, particularly in the context of war and collective memory in Ukraine.